The Religious Principles of Labor Productivity Based on Subject-Content Analysis of Qur'anic Verses Looking at the Country's Five-Year Development Laws - Fatemeh Zeinoddini; Mehdi Toghyani; Mohammad Etrat Doost (Justārhā-yi iqtiṣādī (Online), 2020)
One of the main questions in the field of economics is identifying the factors influencing labor productivity. One of the presuppositions in this regard is the influence of religious values as a fundamental motivating factor on the Muslim workforce, which is influenced by Islamic beliefs and the crystallization of faith in these beliefs can be seen in his behavior. Based on this premise, in order to analyze the behaviors of this important factor of production, it is necessary to discover strategies to strengthen his productivity and influence the quality of human resource performance and extract a list of religious principles affecting the Muslim labor force. However, what is of great importance in such research is the use of appropriate research methods to refer to religious sources to discover appropriate propositions and provide a management model based on which a systematic program for training and productivity growth can be developed. For this reason, this study attempts to combine the two methods of interdisciplinary research "content analysis" and "subject-scientific interpretation" to extract the religious values affecting labor productivity. Also, the alignment of the extracted components with the five-year development plans of the country has been examined along this path. The results indicate that many factors beyond what economic and managerial scholars have stated have had an impact on the workforce and that it is necessary to pay close attention to the teachings of the Islamic religion in the process of transformation and localization of science.